Synthesis and photochemical response of Ru(II)-coordinated double-decker silsesquioxane - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2018)
A double-decker silsesquioxane based bis(terpyridine) ruthenium(II) complex (2Tpy/Ru-DDSQ), a member of the polyhedral oligomeric silsesquioxane (POSS) class, has been synthesized. Its structure has been characterized using comprehensive techniques such as nuclear magnetic resonance (H-1 NMR) spectroscopy, X-ray photoelectron spectroscopy (XPS), and UV-visible spectroscopy. This work not only deals with the synthesis of 2Tpy/Ru-DDSQ but also provides the first comprehensive investigation based on the photoluminescence and electrochemical features of a POSS member. With this structure, an efficient anodic photocurrent response has been obtained. This result has been attributed to the perfect arrangement of ruthenium(II)-bis(terpyridine) (tpy) ([Ru(Tpy)(2)](2+)) moieties in the DDSQ nano building blocks. Therefore, 2Tpy/Ru-DDSQ can be considered as a promising candidate for the development of new generation photosensitizers.
Keywords: METALLO-SUPRAMOLECULAR POLYMERS; SURFACE-PLASMON RESONANCE; SULFATE MICELLAR-SOLUTION; RUTHENIUM(II) COMPLEXES; BUILDING-BLOCKS; NETWORKS; CORE; LUMINESCENCE; NANOPARTICLE; ENHANCEMENT